Educational Transformation: Opportunities and Challenges in the Digital Age - Ikmah Wati; Resultan Aqshal Hafizh Sukamto (proceedings.icesy, 2026)
Educational transformation in the digital era presents new dynamics that require the education system to adapt to technological advancements. The rapid development of information and communication technology creates significant opportunities in the world of education to improve the quality of education through digital innovation. On the other hand, educational transformation in the digital era presents significant challenges such as the digital divide, limited digital literacy, low digital ethics, and a lack of preparedness among educators in integrating technological advancements into learning. This study aims to analyze the opportunities and challenges of education in the digital era, as well as formulate relevant strategies in facing digital transformation. This study uses qualitative methods that refer to literature studies. The results of this study indicate that the success of digital transformation in education depends on the synergy between technological innovation, the role of educators, and sustainable inclusive strategies and policies. The recommendation in this study is the need for good cooperation between various parties, including the government, institutions, the community, educators, and stakeholders in facing digital transformation in education.